UiTM Perak lecturers bagged medals in i2CreaTE (International Innovation, Creativity and Technology Exhibition) 2019 / Mahizan Hijaz Mohammad - Mohammad, Mahizan Hijaz (Corporate Communication Unit Universiti Teknologi MARA, Perak Branch, 2019)
On April 12, 2019, several lecturers from Faculty of Architecture, Planning and Surveying UiTM Perak Branch, Seri Iskandar Campus had won Gold Medal with their innovation entitled Architectural Defects Tracker for Public Private Partnership Projects. The group members were Sr Hasnan Hashim, Assoc. Prof Sr. Dr. Adi Irfan Che Ani and Dr Kharizam ismail.